Prognostic impact of B-cell lymphoma 6 in primary CNS lymphoma. Issue 7 (26th March 2015) - Kreher, Stephan; Jöhrens, Korinna; Strehlow, Felicitas; Martus, Peter; Borowiec, Kathrin; Radke, Josefine; Heppner, Frank; Roth, Patrick; Thiel, Eckhard; Pietsch, Torsten; Weller, Michael; Korfel, Agnieszka
Abstract: Background: We investigated the prognostic significance of B-cell differentiation status and common B-cell differentiation markers in a post hoc analysis of 119 patients with primary CNS lymphoma (PCNSL) homogeneously receiving high-dose methotrexate (HDMTX)–based chemotherapy within the prospective G-PCNSL-SG1 trial. Methods: We evaluated protein expression of B-cell lymphoma 2 (BCL2), BCL6, CD10, and multiple myeloma oncogene 1/interferon regulatory factor 4 (MUM1/IRF4) by immunohistochemistry and analyzed the association with survival. Results: The median follow-up of all patients was 67.5 months. Median progression-free survival (PFS) was 10.61 months (95% CI: 4.23–17.00). Median overall survival (OS) was 28.85 months (95% CI: 17.96–39.73). Eighty-nine tumors expressed BCL2 (92.7%), 24 (20.5%) expressed CD10, 60 (54.1%) expressed BCL6, and 87 (79.0%) expressed MUM1/IRF4. On the basis of the Hans algorithm, 80 tumors (73.4%) were classified to the non–germinal center B group, suggesting a post–germinal center origin of PCNSL. Expression of BCL6 (cutoff point 30%), but none of the other markers, was associated with shorter PFS ( P = .047) and OS ( P = .035). On multivariate analysis, BCL6 expression was associated with shorter PFS (hazard ratio: 1.95, 95% CI: 1.22–3.12, P = .005) but not OS (hazard ratio: 1.85, 95% CI: 0.71–4.80, P = .21). Classification according to Hans algorithm and expression status of the single B-cell markers BCL2, CD10, and MUM1/IRF4 did not correlate with prognosis. Conclusion: The findings are limited by the fact that only 23% of all G-PCNSL-SG1 patients could be included in the analysis. If validated in an independent cohort, BCL6 may assume clinical relevance as an unfavorable prognostic biomarker in PCNSL.